Structural relaxations, vibrational dynamics and thermodynamics of vicinal surfaces - Rahman, Talat S.; Kara, Abdelkader; Durukano lu, Sondan (IOP Publishing, 2003)
We present here a summary of the calculated structural, dynamical and thermodynamical properties of a number of vicinal surfaces of fcc metals with the aim of identifying trends in their characteristics. In general, multilayer relaxations indicate a contraction in the bonds between surface atoms except for that of the least undercoordinated surface atom ('corner') whose bond length with the nearest neighbour bulk atom displays an impressive expansion. Electronic structure calculations show a rearrangement of charge densities near the steps and the layer resolved density of states highlights the characteristics of the undercoordinated atoms. The frequencies of localized vibrational modes on stepped surfaces point to both softening and stiffening of specific force constants, which lead to enhancement of modes in both the lower and higher ends of the frequency spectrum in the vibrational densities of states. Contributions to the surface vibrational entropy from undercoordinated atoms are found to depend strongly on their atomic coordination and play an important role in determining the step excess free energy for certain step geometries. Comparisons of results are made with available experimental data.